Motivating compliance behavior among offenders: procedural justice or deterrence? - Murphy, Kristina (Criminal justice and behavior, 2016)
Research shows that procedural justice can motivate compliance through the mediating influence of either legitimacy or social identity. Using three waves of longitudinal survey data collected from 359 tax offenders, we examine whether procedural justice is important to offenders? decisions to comply with future tax obligations despite fear of sanctions, and whether legitimacy and social identity processes mediate the relationship between procedural justice and compliance. Our results reveal that (a) legitimacy mediates the effect of procedural justice on compliance, (b) social identity mediates the procedural justice/compliance relationship, (c) identity seems to matter slightly more than perceptions of legitimacy when predicting tax compliance, and (d) perceived risk of sanction plays a small, but counterproductive role in predicting tax compliance. We conclude that normative concerns dominate taxpayers? compliance decisions. Implications are relevant for understanding behavioral compliance and how procedural justice can motivate such behavior.